Monetary Returns to College Education, Student Ability, and College Quality - Weisbrod, Burton A.; Karpoff, Peter (The Review of Economics and Statistics, 1968)
This paper attempts to shed new light on the extent to which college education brings financial returns. It recognizes the existence of a number of variables that are likely to affect the financial returns that education produces for a given person -particularly the student's ability and motivation, and the quality of his schooling. It attempts to isolate returns to education from returns to these other related variables.